SPEAKING BACK TO EUROPEAN’S IDEA OF GREATNESS IN THE MOOR’S ACCOUNT (2014) BY LAILA LALAMI - Indah Sri Wahyuni; Desvalini Anwar (Universitas Negeri Padang, 2019)
The purpose of this analysis is to expose the issue of speaking back to European’s idea of greatness which is done by a Moorish slave.Fictional devices such ascharacter, plot (conflict), and setting are used to analyze this novel. The analysis is done through text and context-based interpretation. This study relates to the concept of orientalism and otherness by Edward W.Said. The result of this study shows the character succeeds to speak back to European’s idea of greatness by showing his dignity and his high intelligence.